Examining the effect of imaginary short story activities in Turkish courses on the higher level thinking skills of eighth grade students - Nurullah Aydın; Vahit Ağa Yıldız (Humanities & Social Sciences Communications)
Abstract Short stories stand out as a type of writing that is thought to affect distinct language skills. This study investigates how activities supported by imaginative short stories in Turkish lessons affect eighth-grade students’ higher-level thinking skills. The research employed a mixed-method, sequential explanatory design. In this context, we first collected the quantitative data for the experimental study. We then collected qualitative data through observation and interviews to explain and support the quantitative data. We determined the sample size by considering the central exam success rankings from the previous year and the socio-economic environment, resulting in a total of 46 students in two different classes within a single suitable school. We collected data through the high-level thinking skills test, as well as observations and semi-structured interviews. We analyzed quantitative data using paired and independent sample t-tests, as well as qualitative data using thematic analysis. As a result of the research, we determined that imaginative short stories significantly increased students’ skill test scores and retention levels. In addition, a significant difference was found between the skill test scores of the two groups. The researchers’ observations and the results obtained from the interviews confirmed that the activities achieved the desired results and had positive effects on the students. In this respect, it also supported the quantitative findings. Given its originality, more studies on this topic are required to reach more generalizable results. In particular, the use of imaginative short stories in the education of different languages can help demonstrate the effectiveness of such texts.